Technologie, matières premières et pétrole : vers un monopole bilatéral? - Ayoub, Antoine (L'Actualité économique, 1977)
AbstractWhat is the appropriate economic policy for primary commodity producing developing countries given that industrialized countries are specialized in the production of technological progress? Integrating the concept of product life cycle to the static theory of comparative advantage, Harry Johnson has argued that free trade will, by spreading the technology, dissolve the monopoly in technology, and thus constitutes the only policy capable of transmitting growth from one country to another. This article criticizes this thesis on the following points: 1) A rigorous interpretation of the concept of product life cycle and of the underlying assumptions suggests that only industrialized countries present the necessary conditions for the location of the production of exportable technological progress. 2) It follows that the monopoly of the industrialized countries is not temporary but dynamic and self renewing. 3) Free trade, in this case, will only reinforce the negative effects of this monopoly on international specialization and, therefore, reinforce the disparities between industrialized and developing countries. Given the absence of a supranational authority which could intervene against this monopoly, it is appropriate to consider the limits of the bilateral monopoly policy which the developing countries will apply, based on their primary commodities, and the role that OPEC can play in this context.